Holocaust in the Raseiniai County: Annihilation of the Jewish Communityin the Viduklė Rural District (June–August 1941) - Buchaveckas, Stanislovas (Genocidas ir rezistencija, 2010)
The article continues the holocaust research in the Raseiniai County, which was started with the paper about the massacre of Jews in the Kražiai rural district (see Genocide and Resistance, 2009, No. 2(26). The Viduklė rural district was known for the friendly Jewish and Lithuanian relations. Lithuanian F. Stanevičius around 1870 built a brick synagogue (ruined in 1960) in Viduklė. Here in 1940–1941, the occupant Bolshevists did not succeed in opposing the population on the national grounds; the anti-Soviet underground operated actively. During the anti-Soviet June 1941 Uprising, the squad of the rebels did not manifest itself more prominently, since already on June 23 the German army invaded the rural district territory. On that day, the Red Army and German soldiers massacred a big number of the civilian population, and the shooting of two Jews on the racist grounds may be considered as the beginning of the holocaust in the Raseiniai County. The Nazis did not succeed in involving a squad of rebels into the annihilation of the Jews (as it happened in Kražiai), since it decayed. In Viduklė, there were no Jewish pogroms. The Nazis found few local allies. Just several men entered the auxiliary police. The rural district public police avoided participating in the actions against the Jews.Two Jewish ghettos, separately for men and women (with children), were organized. The men’s ghetto in the Viduklė railway station settlement (here also the Jewish men from the Nemakščiai rural district were imprisoned) was guarded by the German soldiers, and the commandant tortured the prisoners sadistically. The Jewish women with children from the Viduklė rural district were confined in the synagogue.The German “professional” killers at first shot the prisoners in the men’s ghetto (camp) (it is considered that there were 243 people, including, probably, about 80 Jews from Viduklė). The execution was not included into the 1 December 1941 bloody report by 3/A operational squad leader K. Jaeger. After several weeks, on August 22, 1941, Jewish women with children (no less than 81 persons) were shot at the township Jewish cemetery. The execution was carried out by a group of Lithuanian killers who came by lorry from the town of Raseiniai, with the aid of several local helpers. The holocaust in the rural district demanded 160–170 victims. Quite a number of rural district inhabitants participated in rescuing and hiding Jews, mostly brought from other places. The Jews from the Viduklė rural district who experienced resignation did not take advantage of the close relations with Lithuanians, who offered help and possibilities for several tenths of Jews from the rural community to save themselves.
Keywords: Lithuania; German occupation; Holocaust; Raseiniai